Pengaruh Peran Mediasi, Digital Marketing Dan Brand Loyality Terhadap Kepuasan Nasabah PT. Bank Syariah Indonesia Di Kantor Cabang Pembantu Tomang Elok - Ananda Pudjito; Mutiah Khaira Sihotang (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Technological developments greatly benefit banking companies as a medium for marketing products, services and services and increasing turnover. Technological advances make a major contribution to the world of marketing. Then, this study aims to analyze the implementation of the application of digital marketing carried out by the company as a measuring tool, to what extent digital marketing is able to increase customer satisfaction in the financial industry and then its positive impact on brand loyalty from the company. This research was conducted at the financial institution Bank Syariah Indonesia KCP Tumang Elok, by taking questionnaires based on a predetermined sample of customers who use products from Bank Syariah Indonesia with 50 respondents. The method used is quantitative with multiple linear regression analysis. Partially, the Mediation variable (X1) has no effect on customer satisfaction with a significant value> 0.05 (0.138> 0.05) and the t-count value < t-table (1.508 < 2.01290). Partially, the Digital Marketing (X2) variable has an effect on Customer Satisfaction (Y). This can be proven by the results of the t test where the t-count is 4.732 and a significant value of 0.000. Then the significant value <0.05 (0.000 <0.05) and the t-count> t-table value (4.732> 0.000). Partially, the Brand Loyalty variable (X3) has an effect on Customer Satisfaction (Y). This can be proven by the test results